A Highly Reactive Oxoiron(IV) Complex Supported by a Bioinspired N3O Macrocyclic Ligand. (17th October 2017) - Monte Pérez, Inés; Engelmann, Xenia; Lee, Yong‐Min; Yoo, Mi; Kumaran, Elumalai; Farquhar, Erik R.; Bill, Eckhard; England, Jason; Nam, Wonwoo; Swart, Marcel; Ray, Kallol
Abstract: The sluggish oxidants [Fe IV (O)(TMC)(CH3 CN)] 2+ (TMC=1, 4, 8, 11‐tetramethyl‐1, 4, 8, 11‐tetraazacyclotetradecane) and [Fe IV (O)(TMCN‐d12 )(OTf)] + (TMCN‐d12 =1, 4, 7, 11‐tetra(methyl‐d3 )‐1, 4, 7, 11‐tetraazacyclotetradecane) are transformed into the highly reactive oxidant [Fe IV (O)(TMCO)(OTf)] + (1 ; TMCO=4, 8, 12‐trimethyl‐1‐oxa‐4, 8, 12‐triazacyclotetradecane) upon replacement of an NMe donor in the TMC and TMCN ligands by an O atom. A rate enhancement of five to six orders of magnitude in both H atom and O atom transfer reactions was observed upon oxygen incorporation into the macrocyclic ligand. This finding was explained in terms of the higher electrophilicity of the iron center and the higher availability of the more reactive S=2 state in1 . This rationalizes nature's preference for using O‐rich ligand environments for the hydroxylation of strong C−H bonds in enzymatic reactions.